2014
DOI: 10.4174/astr.2014.86.3.115
|View full text |Cite
|
Sign up to set email alerts
|

The pattern and significance of the calcifications of papillary thyroid microcarcinoma presented in preoperative neck ultrasonography

Abstract: PurposeTo analyze the incidence and patterns of calcification of papillary thyroid microcarcinoma (PTMC) on neck ultrasonography (NUS) and assess the clinical implications of calcification, especially for neck node metastasis.MethodsThe clinical data of 379 patients with PTMC who underwent thyroidectomy between January and December 2011 were retrospectively analyzed. PTMC lesions were classified into four subgroups according to their calcification patterns on preoperative NUS: microcalcification, macrocalcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 26 publications
4
41
2
1
Order By: Relevance
“…Extrathyroid invasion, multifocality and calcification are all valuable high-risk factors of lymph metastasis of PTMC (4345). PTMC with these pathological characters exhibit more aggressive biological behavior (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrathyroid invasion, multifocality and calcification are all valuable high-risk factors of lymph metastasis of PTMC (4345). PTMC with these pathological characters exhibit more aggressive biological behavior (42).…”
Section: Discussionmentioning
confidence: 99%
“…Shindo et al (44) and Chow et al (48) reported that neck lymph node metastasis was significantly correlated with tumor multifocality. Multiple microcalcifications were recognized as an important feature of malignancy, and PTMC with calcification was detected with a large size and higher lymph node ratio compared with non-calcified lesions (45). Unfortunately, these options remain controversial (34,38).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that intraglandular dissemination and psammoma bodies in normal thyroid tissue occurred more frequently in cases with than in those without nodal metastasis. Both types of lesion may be detected ultrasonographically [25,26]. Small low-echoic lesions with an irregular margin surrounding PTMC are a marker of intraglandular dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of calcification and the molecular mechanism that is responsible for calcification in PTC is still uncertain (2). The rapid proliferation of cancer cells may lead to necrosis, resulting in calcium deposits (16). Histopathologically, calcifications can be seen as psammoma bodies and dystrophic calcifications, or psammoma bodies and stromal calcifications (2).…”
Section: Discussionmentioning
confidence: 99%